The tree grant money is foliating the community (Cimarron, New Mexico Cimarron Legend, 1992)
Photo Article in the Cimarron legend of three planters planting the trees that were bought with the grant money.
Master List item # 112
File location is in the Raton File Cabinet
Keywords: Grants; Trees; Planting; Cimarron, New Mexico